From Romeo and Juliet to Rosaline & Benvolio: Refashioning Shakespearean Teenage Lovers (Altre Modernità, 2017)
In this essay I analyse a number of narrative retellings of Romeo and Juliet for a Young Adult audience. I focus on three novels which, interestingly, replace the star-crossed lovers, with a couple of minor characters, Benvolio and Rosaline: Lisa Fiedler’s Romeo’s Ex. Rosaline’s Story (2006), Melinda Traub’s Still Star Crossed (2013) and Rachel Caine’s Prince of Shadows (2014). In thse versions Rosaline and Benvolio are given centre stage and narrative voices which open up new narrative possibilities; they end up playing a different and a bigger part than in the original play, but firmly refuse that of the victim to the old generation’s decisions and actions. By exploring motivation, establishing new links between the characters, and having narrators pass authoritative moral judgements, all these texts negotiate with well-established critical interpretations of the central characters, often challenging and channeling them into unexpected critical directions. In a way, these retellings “fix” the original “dangerous” characters Romeo and Juliet, by bringing in new characters as mediators, or expand existing secondary characters in order to make them fit into contemporary notions of teenage role models.